Study of the post tuberculosis lung diseases and the impact of various patient and disease related factors on its occurrence - Gali, Jayasri Helen; Varma, Harsha Vardhana; Badam, Aruna Kumari (International Journal of Advances in Medicine, 2019)
Background: More than fifty percent of the cured cases of pulmonary tuberculosis develop some form of chronic pulmonary dysfunction. It can present with varying degrees of lung damage, ranging from minimum functional abnormalities to severe forms of dysfunction that can be an important cause of death. Objective of the study to identify the various Post Tuberculosis Lung Diseases (PTBLDs) and to study impact of the patient and disease related factors on its occurrence. Methods: Cross-sectional, observational study was conducted in 134 adult, post tuberculosis patients, aged between 18-65 years, who have completed at least one year after the end of anti-tubercular treatment. All symptomatic post TB lung disease patients coming to the pulmonology out-patient clinic at the Apollo Institute of Medical sciences and Research were included in the study. Results: Majority were more than 50 years (35.3%) and males (59.4%). Majority were from urban areas (70.7%), low social class (72.2%), and unskilled workers (56.4%). Most common symptom was cough in 74.4% cases. Majority of the cases had symptoms from one week to one month i.e. 47.4%. Only eight cases were found out to be very prompt in reporting their symptoms. 39 cases had some or the other co-morbidity. Current chest X-ray status was normal in only three cases. Mean FEV1 was 1.38 which increased to 1.52; mean FVC was 1.23 which increased to 1.58; mean FEV1/FVC was 67.37 which increased to 72.76 after giving the bronchodilator. 78(58.6%) cases had obstructive and 27(20.3%) had restrictive lung disease. In 30 cases the disease was reversible. Majority of the cases were of pulmonary fibrosis followed by bronchiectasis. Conclusion: Further studies are needed to develop approaches for the prevention, care and treatment of patients with post TBLD.